Inclusion of calcium oxide in sugarcane silage under different particle sizes on performance of dairy cows - Andrade, Weudes Rodrigues; de Paula Machado, Thiara Jacira Vicuna Mendes Oliveira; David, Gabriel Santos Souza [UNESP]; Pires, Aureliano José Vieira; de Carvalho, Gleidson Giordano Pinto; dos Santos Guimarães Martins, Susi Cristina; de Sousa, Luiz Carlos Oliveira (Springer Nature, 2023)
Our objective was to evaluate voluntary intake, apparent digestibility, performance, and nitrogen balance of dairy cows fed sugarcane silage under different particle sizes treated or not with calcium oxide (CaO). Eight F1 Holstein/Zebu cows, with body weight of 521.5 ± 55.17 kg, and 60 ± 10 days in milk were used, distributed into two simultaneous 4 × 4 Latin squares. The treatments were composed of sugarcane into two particle sizes (15 and 30 mm) with and without the addition of CaO (10 g/kg of natural matter), being the treatments compared according to a 2 × 2 factorial arrangement. Data were analyzed by the MIXED procedure of SAS. The intake of dry matter (13.05 kg/day), crude protein, non-fibrous carbohydrates, and neutral detergent fiber was not modified (P > 0.05) by the inclusion of the calcium oxide, nor by particles size and interaction among both. However, there was interaction between CaO and particle size on dry matter digestibility (P = 0.002), being that the CaO was effective in promoting greater DM digestibility in silages with larger particle size. The milk yield and composition were also not affected by the diets (P > 0.05), similarly for nitrogen balance (P > 0.05). The addition of CaO to sugarcane silage with different particle sizes (15 and 30 mm) does not affect the milk yield and composition of dairy cows, nor the nitrogen balance. However, when CaO is added to the sugarcane silage under larger particle sizes, there are benefits in DM digestibility.
Keywords: Alkaline treatments; Animal feed; Digestibility; Milk